Bis(diphenylphosphino)amines-containing ruthenium cymene complexes as potential anti-Mycobacterium tuberculosis agents - Silva, Juliana P. da; Silva, Isabel C. [UNESP]; Pavan, Fernando R. [UNESP]; Back, Davi F.; Araujo, Marcio P. de (Elsevier B.V., 2017)
Several ruthenium complexes have been investigated regarding anti-Mycobacterium tuberculosis (anti-MTb) activity, with some diphosphine-containing ruthenium complexes comparable to first and second line drugs. However, to the best of our knowledge, there is no P-N-P-containing ruthenium complexes applied as metallodrugs. Thus, this study focused on the synthesis, characterization and anti-MTb activity of a new series of coordination compounds with general formula [RuCl(eta(6)-p-cymene)(P-N-R-P)]X (R = CH2Py (Py = pyridine) - [1a], CH2Ph (Ph = phenyl) - [1b], Ph - [1c] and p-tol (p-tol = p-tolyl) - [1d]; X = PF6- or BF4-). The complexes were fully characterized by NMR (H-1, P-31{H-1}), vibrational spectroscopy (FTIR), ESI-MS, molar conductance, elemental analysis and X-ray diffraction studies. The molecular structures of [1a]center dot PF6, [1c]center dot BF4 and [1d]center dot PF6 were determined and confirm the spectroscopic and ESI-MS data. The complexes were used in anti-MTb trials, and the preliminary results are presented. The complexes are promising anti-MTb agents with MIC90 (Minimum Inhibitory Concentration of compounds required to inhibit the growth of 90% of MTb) values comparable with the Ethambutol, the reference drug used in this work, and complex [1a]center dot BF4 presented the highest selectivity index.